2018
DOI: 10.1002/ajmg.a.38610
|View full text |Cite
|
Sign up to set email alerts
|

Extending the phenotype associated with the CSNK2A1‐related Okur–Chung syndrome—A clinical study of 11 individuals

Abstract: Variants in the Protein Kinase CK2 alpha subunit, encoding the CSNK2A1 gene, have previously been reported in children with an intellectual disability and dysmorphic facial features syndrome: now termed the Okur-Chung neurodevelopmental syndrome. More recently, through trio-based exome sequencing undertaken by the Deciphering Developmental Disorders Study (DDD study), a further 11 children with de novo CSNK2A1 variants have been identified. We have undertaken detailed phenotyping of these patients. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 19 publications
3
60
1
Order By: Relevance
“…To date, many researchers have worked to reveal interactions between genetic variants and disease phenotypes. Recently, COMMUNICATIONS BIOLOGY | https://doi.org/10.1038/s42003-020-0755-1 ARTICLE COMMUNICATIONS BIOLOGY | (2020) 3:33 | https://doi.org/10.1038/s42003-020-0755-1 | www.nature.com/commsbio genome-wide quantification analyses have shown that rare mutations are found in normal tissue, whereas risk variants from neurodevelopmental disorder patients are common genetic variants, implying that non-rare genetic variants may cause genetic disease in some patients [50][51][52][53][54][55] . In this study, we showed that correction of the ATP7A M1311V mutation can rescue the function of MNs derived from cells of one ALS patient of Ashkenazi Jewish descent.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many researchers have worked to reveal interactions between genetic variants and disease phenotypes. Recently, COMMUNICATIONS BIOLOGY | https://doi.org/10.1038/s42003-020-0755-1 ARTICLE COMMUNICATIONS BIOLOGY | (2020) 3:33 | https://doi.org/10.1038/s42003-020-0755-1 | www.nature.com/commsbio genome-wide quantification analyses have shown that rare mutations are found in normal tissue, whereas risk variants from neurodevelopmental disorder patients are common genetic variants, implying that non-rare genetic variants may cause genetic disease in some patients [50][51][52][53][54][55] . In this study, we showed that correction of the ATP7A M1311V mutation can rescue the function of MNs derived from cells of one ALS patient of Ashkenazi Jewish descent.…”
Section: Discussionmentioning
confidence: 99%
“…There are thousands of rare human disorders caused by a single deleterious, proteincoding genetic variant 1 . However, patients with the same genetic defect can have different clinical presentation [2][3][4] , and some individuals carrying known disease-causing variants can appear unaffected 5 . What explains these differences?…”
mentioning
confidence: 99%
“…These results indicate that the OCNDS-associated mutations may alter the morphology and structure of primary cilia. OCNDS exhibits overlapping clinical features with ciliopathies (20,43,46,47). Our work, therefore, establishes a new link between Csnk2a1 and cilia regulation and raises the possibility that OCNDS might be linked, at least partially, to disrupted cilia structure or function.…”
Section: Csnk2a1 Is Required For Cilium Stabilitymentioning
confidence: 51%
“…Dominant mutations in Csnk2a1 were recently associated with a human syndrome known as Okur-Chung neurodevelopmental syndrome (OCNDS) (20,(40)(41)(42)(43)(44). This disorder is characterized by dysmorphic facial features as well as neurological phenotypes, bearing some similarities to human ciliopathies.…”
Section: Csnk2a1 Is Required For Cilium Stabilitymentioning
confidence: 99%
See 1 more Smart Citation